Mitsunobu and related reactions: advances and applications - Swamy, K. C. Kumara; Kumar, N. N. Bhuvan; Balaraman, Ekambaram; Kumar, K. V. P. Pavan (Chemical Reviews, 2009)

Alkynyl and phosphonyl substituted nucleobases: a case of thermally induced conformational polymorphism - Swamy, K. C. Kumara; Allu, Srinivasarao; Srinivas, Venu; Balaraman, Ekambaram; Kumar, K. V. P. Pavan (Crystal Growth & Design, 2011)
Substituted nucleobases with alkynyl and phosphonyl groups were investigated in the context of supramolecular interactions and possible use toward synthesis of nucleoside phosphonic acids (NPAs). The adeninyl compound (adeninyl-N-9)-CH2CH2CH2CH2C≡CH exhibits conformational polymorphism as revealed by X-ray structures determined at 200 and 298 K. Interestingly, in the compound (adeninyl-N-9)-(CH2)15CH3, the long aliphatic carbon chain does not show disorder. A rather unusual bending of alkyl chain, likely due to C–H···O interactions, is observed in the case of the thymine compound (thyminyl)-CH2CH2CH2C≡CH that possesses a terminal alkyne group. The powerful hydrogen bond acceptor property of the phosphoryl oxygen (P═O) does not perturb (unless assisted by other hydrogen bonding partners) the homo base-pairing in the structures of most of the phosphonyl substituted nucleobases studied.